Doping Mo into NiFe LDH/NiSe Heterostructure to Enhance Oxygen Evolution Activity by Synergistically Facilitating Electronic Modulation and Surface Reconstruction. Issue 20 (19th September 2022) - Gan, Yonghao; Li, Zhi; Ye, Ying; Dai, Xiaoping; Nie, Fei; Yin, Xueli; Ren, Ziteng; Wu, Baoqiang; Cao, Yihua; Cai, Run; Zhang, Xin; Song, Weiyu
Abstract: It is of great significance to design highly efficient electrocatalysts with abundant earth elements instead of precious metals for water splitting. Herein, Mo‐doped NiFe‐layered double hydroxides/NiSe heterostructure (Mo‐NiFe LDH/NiSe) was fabricated by coupling Mo‐doped NiFe LDH and NiSe on nickel foam (NF). The heterostructure electrocatalyst showed ultra‐low overpotential (250 mV) and remarkable durability for oxygen evolution reaction (OER) at 150 mA cm −2 . Both theoretical and experimental results confirmed that Mo doping and interfacial synergism induced the interfacial charge redistribution and the lifted d‐band center to weaken the energy barrier ( EB ) of the formation of OOH * . Mo doping also facilitated the surface reconstruction of NiFe LDH into Ni(Fe)OOH as the active sites under electro‐oxidation process. This work provides a facile strategy for electronic modulation and surface reconstruction of OER electrocatalyst by transition metal doping and heterostructure generation. Abstract : At the interface : Doping Mo into NiFe layered double hydroxides (LDH) and formation of heterojunction with NiSe synergistically induce the redistribution of electrons at the interface, raise the d‐band center to optimize the energy barrier for the formation of OOH *, and promote the surface reconstruction into Ni/FeOOH, thereby facilitating oxygen evolution reaction.